Delayed Magnetic Resonance Imaging in Patients With Cervical Spinal Cord Injury Without Radiographic Abnormality. Issue 16 (15th August 2016) - Ouchida, Jun; Yukawa, Yasutsugu; Ito, Keigo; Katayama, Yoshito; Matsumoto, Tomohiro; Machino, Masaaki; Inoue, Taro; Tomita, Keisuke; Kato, Fumihiko
Abstract : Study Design: A prospective imaging study to develop diagnostic criteria. Objective: The aim of this study was to investigate image findings on delayed magnetic resonance imaging (MRI) after the acute phase of spinal cord injury without radiographic abnormality (SCIWORA) and their relationship with symptom severity. Summary of Background Data: MRI is used to diagnose acute neurological injury, with increased signal intensity (ISI) and prevertebral hyperintensity (PVH) often seen in patients with SCIWORA; however, changes after the acute phase are unclear. Methods: We included 68 patients diagnosed with SCIWORA within 48 hours of injury. We then compared their acute (within 2 days) and delayed (after 2 weeks) MRI images. ISI grade (0–3) and ISI and PVH ranges (relative to the C3 vertebral height) were measured. Neurological status at admission and 2 weeks after injury was assessed by the Japanese Orthopaedic Association scoring system for cervical myelopathy (JOA score) and the American Spinal Injury Association impairment scale. Results: For acute MRI, the rates of grade 0, 1, and 2 ISI were 4, 54, and 10 patients, respectively. For delayed MRI, the rates of grade 0, 1, and 2 ISI changed to 3, 31, and 34 patients, respectively. ISI ranges reduced in delayed MRI, but there was no significance. PVH ranges were 3.0 ± 1.7 in acute MRI, and reduced to 1.3 ± 0.9 with significant difference ( P < 0.001). There were significant negative correlations with the JOA score for ISI grades on delayed MRI only ( r = −0.49). However, there were significant negative correlations with the JOA score for the PVH range on both the acute ( r = −0.55) and delayed ( r = −0.46) MRI. Conclusion: When comparing acute and delayed MRI, there were significant differences in ISI and PVH findings. Delayed MRI also reflected the clinical symptom severity, giving useful information about the state of the spinal cord. Level of Evidence: 3